InSAR measurements of compaction and subsidence in the Ganges‐Brahmaputra Delta, Bangladesh. Issue 8 (22nd August 2014) - Higgins, Stephanie A.; Overeem, Irina; Steckler, Michael S.; Syvitski, James P. M.; Seeber, Leonardo; Akhter, S. Humayun
Abstract Many of the world′s largest river deltas are sinking due to sediment loading, compaction, and tectonics but also recently because of groundwater extraction, hydrocarbon extraction, and reduced aggradation. Little is known, however, about the full spatial variability of subsidence rates in complex delta systems. This study reconstructs subsidence rates in the eastern portion of the Ganges‐Brahmaputra Delta (GBD), Bangladesh, covering more than 10, 000 km2 at a high spatial resolution of 100 m. The map was produced using Interferometric Synthetic Aperture Radar (InSAR) covering the period 2007 to 2011. Eighteen Advanced Land Observing Satellite Phased‐Array L‐band SAR scenes were used to generate 30 interferograms calibrated with GPS. Interferograms were stacked to yield average subsidence rates over the study period. Small Baseline Subset‐InSAR was then applied to validate the results against an additional GPS record from Dhaka, Bangladesh. Land subsidence of 0 to > 10 mm/yr is seen in Dhaka, with variability likely related to local variations in shallow subsurface sediment properties. Outside of the city, rates vary from 0 to > 18 mm/yr, with the lowest rates appearing primarily in Pleistocene Madhupur Clay and the highest rates in Holocene organic‐rich muds. Results demonstrate that subsidence in this delta is primarily controlled by local stratigraphy, with rates varying by more than an order of magnitude depending on lithology. The ability of L‐band InSAR to differentiate between stratigraphic units in this humid, vegetated subtropical river delta demonstrates the power of interferometry as a tool for studying the subsurface in deltaic environments.